Pengaruh Diversifikasi Pendapatan Non-Bunga Terhadap Profitabilitas Bank di Indonesia - Sasmita Restu Hutami; Dara Noviandy; Susy Muchtar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the effect of non-interest income diversification on the profitability of commercial banks in Indonesia, measured by Return on Assets (ROA). The data used is secondary data from annual reports of 41 banks listed on the Indonesia Stock Exchange for the period 2020–2024, resulting in a total of 205 observations. The analysis method employed is panel data regression using EViews 12. Non-interest income diversification is measured using the Herfindahl-Hirschman Index (HHI), while the independent variables include bank size (lnAS), non-performing loans (NPL), cost-to-income ratio (CIR), and loan-to-asset ratio (LTA). The findings show that non-interest income diversification and CIR have a negative and significant impact on ROA, whereas lnAS, NPL, and LTA do not have a significant effect. These results suggest that bank profitability is more influenced by operational efficiency and the management of non-interest income rather than asset or credit expansion. Therefore, bank management should focus their strategies on cost control and the sustainable optimization of non-intermediation income.